Hubungan Antara Usia Ibu dan Paritas dengan Kejadian Anemia pada Ibu Hamil di Wilayah Kerja Puskesmas Jatiroto Kabupaten Lumajang - Wahyuni, Dwi; Farianingsih, Farianingsih; Rohmatin, Homsiatur (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Anemia in pregnancy is a national problem because it reflects the socio-economic welfare of the community, and has a very large influence on the quality of human resources. Pregnant anemia is called potential danger to mother and child (potentially endangering mother and child), that's why anemia requires serious attention from all parties involved in health services at the forefront. This study aims to determine the relationship between maternal age and parity with the incidence of anemia in pregnant women in the Jatiroto Health Center Work Area.This research was conducted using correlational analytic research method with cross sectional approach. The sample of this study was all pregnant women who were examined at the Jatiroto Health Center, Lumajang Regency in July 2022 as many as 60 respondents were taken by the total sampling method.The results of the study found that almost half of the respondents had an age of <20 years as many as 28 respondents (46.7%). Most of the respondents have parity in the multipara category as many as 42 respondents (70%). And almost half of the respondents had anemia in the normal category as many as 21 respondents (35%).From the results of the analysis, it was found that there was a relationship between maternal age and the incidence of anemia in pregnant women in the working area of ​​the Jatiroto Health Center, Lumajang Regency with p<0.05, namely p = 0.023 and there was a relationship between parity and the incidence of anemia in pregnant women in the working area of ​​the Jatiroto Health Center, District Lumajang with a value of p< 0.05, namely p = 0.024It is hoped that pregnant women and their families can increase awareness to take advantage of the health facilities provided by the government so that pregnant women can better monitor their health conditions, especially Hb levels to prevent anemia.